Eteronomia ed elezione. Derrida e l’elogio della psicoanalisi - Di Martino, Carmine (Bollettino Filosofico, 2021)
Inserted in the wider debate around the relationship between Derrida and psychoanalysis, this essay investigates the different status of ipseity arising from the encounter between deconstruction and psychoanalysis. The aim is to show how Derrida provides us with a “positive” knowledge about the “subject” – a “subject” that is divided, differentiated, irreducible to the conscious intentionality of an egological pole – and its genealogy, via some word-concepts: heteronomy, election, response. Keywords: Derrida, Election, Heteronomy, Psychoanalysis, Response